Diffusion‐weighted 3D multislab echo planar imaging for high signal‐to‐noise ratio efficiency and isotropic image resolution. Issue 6 (28th January 2013) - Engström, Mathias; Skare, Stefan
<x xml:space="preserve">Abstract</x> Purpose To acquire isotropic high‐resolution, signal‐to‐noise ratio (SNR) efficient, 3D encoded diffusion‐weighted MRI data. Methods Multiple Fourier encoded slabs were combined into one full volume, using a generalized autocalibrating partially parallel acquisitions (GRAPPA) accelerated diffusion‐weighted 3D multislab echo planar imaging (EPI) sequence with 2D phase navigation and in‐plane motion correction. Results Reconstructed data with 1.5‐mm3 nominal resolution is presented and shown under the influence of motion and with variable slab thicknesses. The SNR efficiency between diffusion‐weighted 3D multislab EPI and DW 2D ss‐EPI is compared. Finally, a 1.3‐mm3 full brain scan with 45 diffusion directions is presented. Conclusions Diffusion‐weighted 3D multislab EPI has been presented as an alternative sequence for high‐resolution and high‐SNR full brain coverage diffusion studies. Compared with the gold standard 2D diffusion‐weighted single‐shot Echo Planar Imaging, the SNR efficiency is significantly higher. Magn Reson Med 70:1507–1514, 2013. © 2013 Wiley Periodicals, Inc.